Bandgap-selective chemical doping of semiconducting single-walled carbon nanotubes - Li, L; Nicholas, R (2004)
Bandgap-selective p doping of single-walled carbon nanotubes (SWCNTs) in aqueous surfactant suspensions is reported. Nanotubes with narrower bandgaps are preferentially doped by hexacyanoferrate (III), as observed by optical absorption. The bandgap absorption characteristics, which are controlled by the chemical potential, can be reversibly adjusted by controlling the oxidation potential of the dopants through the pH value. The origin of the selective modification of bandgap absorption is electron transfer between the carbon nanotubes and the hexacyanoferrate (III), which preferentially depopulates the valence band in narrower gap nanotubes.